Modified Legendre Rational Spectral Method for Burgers Equation on the Whole Line (Journal of Mathematical Study, 2022)
In this paper, we propose a spectral method for the Burgers equation using the modified Legendre rational functions, and prove its generalized stability and convergence. Numerical results demonstrate the efficiency of the new approach.
Keywords: Burgers equation; spectral method; modified Legendre rational functions; problem on the whole line.